Robust monetary policy in a new Keynesian model with imperfect interest rate pass-through - Rafael Gerke; Felix Hammermann (Deutsche Bundesbank, 2011)
We use robust control to study how a central bank in an economy with imperfect interest rate pass-through conducts monetary policy if it fears that its model could be misspecified. The effects of the central bank's concern for robustness can be summarised as follows. First, depending on the shock, robust optimal monetary policy under commitment responds either more cautiously or more aggressively. Second, such robustness comes at a cost: the central bank dampens volatility in the inflation rate preemptively, but accepts higher volatility in the output gap and the loan rate. Third, if the central bank faces uncertainty only in the IS equation or the loan rate equation, the robust policy shifts its concern for stabilisation away from inflation.
Keywords: E44; E58; E32; 330; optimal monetary policy; commitment; model uncertainty